Statistical Mechanics : Principles and Selected Applications - Hill, Terrell L (New York : Dover Publication, 1987)
Standard text opens with clear, concise chapters on classical statistical mechanics, quantum statistical mechanics, and the relation of statistical mechanics to thermodynamics. Further topics cover fluctuations, the theory of imperfect gases and condensation, distribution functions and the liquid state, nearest neighbor (Ising) lattice statistics, and more.
Includes bibliographical references; Appendix 393-425p.; Index 427-432p.
Keywords: Biology; Ecology; Zoology